2018
DOI: 10.1186/s13058-018-1059-y
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic breast cancer cells overexpress and secrete miR-218 to regulate type I collagen deposition by osteoblasts

Abstract: BackgroundBone is one of the most frequent metastatic sites of advanced breast cancer. Current therapeutic agents aim to inhibit osteoclast-mediated bone resorption but only have palliative effects. During normal bone remodeling, the balance between bone resorption and osteoblast-mediated bone formation is essential for bone homeostasis. One major function of osteoblast during bone formation is to secrete type I procollagen, which will then be processed before being crosslinked and deposited into the bone matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 40 publications
2
60
0
Order By: Relevance
“…Recent studies have highlighted the relationship among exosomes, microRNAs (miRNAs) and collagen in cancer [80][81][82].…”
Section: The Relationship Among Exosomes Micrornas and Collagen In Cmentioning
confidence: 99%
“…Recent studies have highlighted the relationship among exosomes, microRNAs (miRNAs) and collagen in cancer [80][81][82].…”
Section: The Relationship Among Exosomes Micrornas and Collagen In Cmentioning
confidence: 99%
“…There is increased collagen production at the bone metastatic site, whereby secreted collagen molecules are dense, misaligned, and disorganized, further disrupting bone mechanical function (Figure 5b) [66,75]. Liu et al identified that metastatic breast cancer cells secreted miR-218 which directly regulated type I collagen secretion from osteoblasts in the bone niche [76]. The authors further identified elevated levels of miR-218 in blood samples from patients with breast cancer bone metastases, suggesting miR-218 as a possible therapeutic for patients with bone metastatic breast cancer [76].…”
Section: The Bone Extracellular Matrixmentioning
confidence: 99%
“…For instance, the let-7 family members (let-7a, let-7b, and let-7g) have been demonstrated to be poorly-expressed in the patients diagnosed with breast cancer with lymph node metastasis [9]. Previous work further illustrated the targeting relationship between miRNA and collagen in breast cancer [10]. Interestingly, through bioinformatics and a dual luciferase reporter gene assay, COL3A1 was suggested as a direct target of let-7b in neuronal injury [11].…”
Section: Introductionmentioning
confidence: 99%